Microstructure and hot deformation behavior of Cu–Ti–Zr(-Mg) alloys - Zhiyu Han; Meng Zhou; Ke Jing; Chunhe Chu; Yi Zhang; Baohong Tian; Zheng'ao Li; Ziyi Qin; Jin Zou; Xu Li; Huiwen Guo (Journal of Materials Research and Technology)
In this study, the thermal deformation behavior of Cu–Ti–Zr(-Mg) alloys were investigated by Gleeble-1500D. The two alloys were deformed at 700–900 °C with 0.003–10 s−1 strain rate. The intrinsic equations of the two alloys were constructed and calculated thermal activation energies, which indicates that it is improved from 325.67 kJ/mol to 344.03 kJ/mol after Mg addition. The result showed that the hot working area of Cu–Ti–Zr alloy is greatly extended after Mg addition, and rheological instability area is reduced. The morphology of the alloys was observed to analyze thermal behavior. It revealed that Mg elements inhibited the occurrence of dynamic recrystallization and shifted the texture types in the alloys by characterization of EBSD. TEM results showed that the phases during hot deformation in Cu–Ti–Zr–Mg are Cu4Ti and Cu10Zr7, which are in a semi-coherent relationship with the Cu matrix.